Spectroscopic Time Series Performance of the Mid-infrared Instrument on the JWST. (15th March 2023) - Bouwman, Jeroen; Kendrew, Sarah; Greene, Thomas P.; Bell, Taylor J.; Lagage, Pierre-Olivier; Schreiber, Jürgen; Dicken, Daniel; Sloan, G. C.; Espinoza, Néstor; Scheithauer, Silvia; Coulais, Alain; Fox, Ori D.; et al.
Abstract: We present here the first ever mid-infrared spectroscopic time series observation of the transiting exoplanet L 168-9 b with the Mid-Infrared Instrument (MIRI) on the James Webb Space Telescope. The data were obtained as part of the MIRI commissioning activities, to characterize the performance of the Low Resolution Spectroscopy (LRS) mode for these challenging observations. To assess the MIRI LRS performance, we performed two independent analyses of the data. We find that with a single transit observation we reached a spectro-photometric precision of ∼50 ppm in the 7–8 μ m range at R = 50, consistent with ∼25 ppm systematic noise. The derived band averaged transit depth is 524 ± 15 ppm and 547 ± 13 ppm for the two applied analysis methods, respectively, recovering the known transit depth to within 1 σ . The measured noise in the planet's transmission spectrum is approximately 15%–20% higher than random noise simulations over wavelengths 6.8 ≲ λ ≲ 11 μ m. We observed an larger excess noise at the shortest wavelengths of up to a factor of two, for which possible causes are discussed. This performance was achieved with limited in-flight calibration data, demonstrating the future potential of MIRI for the characterization of exoplanet atmospheres.